Histopathologic correlation of Aspergillus endophthalmitis following uncomplicated cataract surgery - Haddock LJ (Dove Medical Press, 2012)
Luis J Haddock,1 Harry W Flynn Jr,1 Sander R Dubovy,1 Rahul N Khurana,2 Peter R Egbert31Department of Ophthalmology, Bascom Palmer Eye Institute, Miami Miller School of Medicine, Miami, FL, 2Northern California Retina Vitreous Associates, Mountain View, CA, 3Department of Ophthalmology, The Byers Eye Institute at Stanford, Stanford University, Palo Alto, CA, USAAbstract: A clinicopathologic correlation between two patients with acute-onset Aspergillus endophthalmitis undergoing enucleation is reported. These two patients presented with pain, redness, and decreased vision following uncomplicated cataract surgery. In both patients, vitreous aspiration and intravitreal injections were the initial treatment followed later by pars plana vitrectomy for clinical worsening. Despite repeated surgical and medical interventions, the clinical course of both patients was prolonged, unsuccessful, and resulted in enucleation for a blind painful eye. Histologic examination of the enucleated specimens showed that, in spite of prolonged local and systemic therapy, there was persistent diffuse infiltration of the anterior chamber and ciliary body by a filamentous mold.Keywords: mold, enucleation, voriconazole, amphotericin B